2015
DOI: 10.13164/re.2015.1050
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Layer Combining of Adaptive Modulation and Truncated ARQ in Multichannel Beamforming MIMO Systems

Abstract: Abstract. In this study the authors provide a cross-layer design of multiple-input-multiple-output (MIMO) systems

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…For example, truncated HARQ is added on top of AMC (adaptive modulation and coding) where the type of modulation and modes of HARQ are changed to adapt to changes in the channel conditions. Studies have shown that the combination of AMC and truncated ARQ makes the systems more robust and also applicable to time limited applications (Liu et al, 2004;Kang et al, 2010;Yang et al, 2012;Ivanis et al, 2015). While AMC and truncated HARQ can separately be employed to deal with varying channel conditions, some studies have been carried out to compare the effects of AMC and truncated HARQ, showing that AMC yields improved performance in noisy channels (Sassioui et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, truncated HARQ is added on top of AMC (adaptive modulation and coding) where the type of modulation and modes of HARQ are changed to adapt to changes in the channel conditions. Studies have shown that the combination of AMC and truncated ARQ makes the systems more robust and also applicable to time limited applications (Liu et al, 2004;Kang et al, 2010;Yang et al, 2012;Ivanis et al, 2015). While AMC and truncated HARQ can separately be employed to deal with varying channel conditions, some studies have been carried out to compare the effects of AMC and truncated HARQ, showing that AMC yields improved performance in noisy channels (Sassioui et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…al., 2012). Attempts have also been taken to apply the cross-layer combining of truncated-ARQ and adaptive modulation to multichannel beam-forming MIMO systems (Ivanis et al, 2015), and in cooperative relay networks employing network coding (Yangi et al, 2016). The main drive in these studies was to show that truncated ARQ/HARQ can lead to improved performance in various types of systems, as well as to establish methods of analysing the truncated ARQ/HARQ systems.…”
Section: Introductionmentioning
confidence: 99%
“…-The analysis results would provide useful insight on the design of 3-D multiple-input-multiple-output (MIMO) beamforming technology and smart antenna array [17][18][19] for fifth generation (5G) networks.…”
Section: Introductionmentioning
confidence: 99%